Updated search for long-lived particles decaying to jet pairs - Aaij, R; Adeva, B; Adinolfi, M; Evans, T; Gandini, P; Gruberg Cazon, B; Hadavizadeh, T; Harnew, N; Hill, D; Jalocha, P; John, M; Jurik, N; et al. (Springer, 2017)
A search is presented for long-lived particles with a mass between 25 and 50GeV/c2 and a lifetime between 2 and 500 ps, using proton–proton collision data corresponding to an integrated luminosity of 2.0fb-1, collected by the LHCb detector at centre-of-mass energies of 7 and 8 TeV. The particles are assumed to be pair-produced in the decay of a 125GeV/c2 Standard-Model-like Higgs boson. The experimental signature is a single long-lived particle, identified by a displaced vertex with two associated jets. No excess above background is observed and limits are set on the production cross-section as a function of the mass and lifetime of the long-lived particle.